Risk assessment at public sector construction projects in Bangladesh: a case study - Mridha, Mohammad Zabed Alam (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2017.